Safety and Clinical Outcomes of Catheter Ablation of Atrial Fibrillation in Patients With Chronic Kidney Disease. (5th December 2016) - ULLAL, ADITYA J.; KAISER, DANIEL W.; FAN, JUN; SCHMITT, SUSAN K.; THAN, CLAIRE T.; WINKELMAYER, WOLFGANG C.; HEIDENREICH, PAUL A.; PICCINI, JONATHAN P.; PEREZ, MARCO V.; WANG, PAUL J.; TURAKHIA, MINTU P.
Catheter Ablation of AF in Chronic Kidney Disease: Introduction: Data regarding catheter ablation of atrial fibrillation (AF) in patients with chronic kidney disease (CKD) is limited. We therefore assessed the association of CKD with common safety and clinical outcomes in a nationwide sample of ablation recipients. Methods: Using MarketScan ® Commercial Claims and Medicare Supplemental Databases, we evaluated 30‐day safety and 1‐year clinical outcomes in patients who underwent a first AF ablation procedure between 2007 and 2011. We calculated frequency of common 30‐day complications and calculated frequencies, incidence rates, and Cox proportional hazards for outcomes at 1‐year postablation. Results: Of 21, 091 patients included, 1, 593 (7.6%) had CKD. Patients with CKD were older (64 years vs. 59 years, P < 0.001) with higher CHA2 DS2 ‐VASc scores (3.2 vs. 1.8, P < 0.001). At 30 days postablation, patients with CKD had similar rates of stroke/TIA (0.13% vs. 0.13%, P = 0.99), perforation/tamponade (3.2% vs. 3.1%, P = 0.83), and vascular complications (2.4% vs. 2.2%, P = 0.59) as patients without CKD, but were more likely to be hospitalized for heart failure (2.1% vs. 0.4%, P < 0.001). In multivariate analysis, there were no significant differences in hazards of AF hospitalization (adjusted HR: 1.02, 95%CI: 0.87–1.20), cardioversion (adjusted HR: 0.99, 95%CI: 0.87–1.12), or repeat AF ablation (adjusted HR: 0.89, 95%CI: 0.76–1.06) at 1 year. Conclusions: Among patients selected for AF ablation, those with and without CKD had similar rates of postprocedural complications although they were more likely to be re‐admitted for heart failure. CKD was not independently associated with AF hospitalization, cardioversion, and repeat ablation. These findings can inform clinical decision‐making in patients with AF and CKD.